2013
DOI: 10.1088/0957-4484/24/32/325601
|View full text |Cite
|
Sign up to set email alerts
|

Quantum Hall effect in fractal graphene: growth and properties of graphlocons

Abstract: Highly dendritic graphene crystals up to 0.25 mm in diameter are synthesized by low pressure chemical vapor deposition inside a copper enclosure. With their sixfold symmetry and fractal-like shape, the crystals resemble snowflakes. The evolution of the dendritic growth features is investigated for different growth conditions and surface diffusion is found to be the growth-limiting step responsible for the formation of dendrites. The electronic properties of the dendritic crystals are examined down to sub-Kelvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 41 publications
1
18
0
Order By: Relevance
“…The flower-like (dendritic) shape 35 , with irregular and multifractal-like edges 35,89,90 , indicates a diffusionlimited growth mechanism. The more regular hexagonal grains 76 , whose edges are shown to be predominantly oriented along the zigzag directions of graphene lattice 76,91 , represent an edge-attachmentlimited growth 77 .…”
mentioning
confidence: 99%
“…The flower-like (dendritic) shape 35 , with irregular and multifractal-like edges 35,89,90 , indicates a diffusionlimited growth mechanism. The more regular hexagonal grains 76 , whose edges are shown to be predominantly oriented along the zigzag directions of graphene lattice 76,91 , represent an edge-attachmentlimited growth 77 .…”
mentioning
confidence: 99%
“…Therefore, to enhance electronic properties of graphene‐based devices, investigations on growth of single‐crystal graphene grains have been motivated. Recent advances in the CVD method have enabled the preparation of single‐crystal graphene grains with several shapes . Among those grains, hexagonal graphene has been the most extensively explored since it was observed on solid copper (Cu) foil .…”
mentioning
confidence: 99%
“…Among those grains, hexagonal graphene has been the most extensively explored since it was observed on solid copper (Cu) foil . Apart from that, triangular, rectangular, four‐lobed, and snow‐like graphene grains have been achieved, demonstrating the great potential in shaping graphene using CVD approach on metal substrates.…”
mentioning
confidence: 99%
“…A qualitative model was proposed, in which the final morphology of graphene was determined by the competition between carbon atoms diffusion along island edges and adatom surface diffusion. Meanwhile, another work showed that highly dendritic graphene crystals resemble snowflakes up to 0.25 mm in diameter that were synthesized inside a copper enclosure . Further characterizations demonstrated that the carbon surface diffusion was the growth‐limiting step and responsible for the formation of dendrites.…”
Section: Size and Morphology Engineering Of Graphene Single Crystalsmentioning
confidence: 99%